The organomercurial 4-aminophenylmercuric acetate, independent of matrix metalloproteinases, induces dose-dependent activation/ inhibition of platelet aggregation - Rosenfeldt, Mathias T.; Valentino, Michael; Labruzzo, Salvatore; Scudder, Lesley; Pavlaki, Maria; Cao, Jian; Vacirca, Jeffrey; Bahou, Wadie F.; Zucker, Stanley (Thrombosis and Haemostasis, 2005)
Matrix metalloproteinases (MMPs) play an important role in many biological and pathological processes including tissue remodeling, wound healing, inflammation, atherosclerosis, and cancer. Numerous publications have supported the concept that activated MMP-2 enhances agonist-induced platelet aggregation and activated MMP-9 inhibits platelet aggregation. In this study, we demonstrated that the organomercurial compound, 4-aminophenyl mercuric acetate (APMA), which is routinely employed to activate latent MMPs at a concentration of 1000 μ M, induces platelet aggregation at low concentration (5 μ M) and inhibits agonist-induced platelet aggregation at concentrations ≥ 50 μ M. Activated MMP-2, MMP-1, and MMP-9, following removal of APMA by ultrafiltration through an anisotropic membrane, exert no independent effect on platelet aggregation. Acetylsalicylic acid and BAPTA inhibited APMA-induced platelet aggregation indicating that the APMA mediated pathway of platelet activation is dependent upon thromboxane and calcium signaling. Zinc chelation with 1,10-phenanthroline, which inhibits zincdependent proteins including metalloproteinases, also abrogated platelet functional responses to APMA. Additional studies will be required to clarify the mechanism of the biphasic effect of APMA on platelet aggregation.
Keywords: Matrix metalloproteinases (MMP); platelet aggregation; 4-aminophenylmercuric acetate (APMA)